Implementation of Termination of Prosecution Based on Restorative Justice: A Study of Normative Dilemmas in the Prosecutor’s Office - Putra, Dewa Gede Natih Dena Darma (KnE Social Sciences, 2025)
The Prosecutor’s Office is one of the institutions in the criminal justice system that has an important position in law enforcement in Indonesia. The authority of the prosecutor’s office includes implementing court decisions in the form of returning criminal assets. In this journal, the problem raised is how the procedure for returning criminal assets is carried out at the Gianyar District Prosecutor’s Office, and whether the implementation of returning criminal assets carried out at the Gianyar District Prosecutor’s Office is in accordance with the principle of transparency. The purpose of writing this journal is to find out the procedure for returning criminal assets at the Gianyar District Prosecutor’s Office and to find out the suitability between the implementation of asset return activities at the Gianyar District Prosecutor’s Office and the principle of transparency. The research method used is the empirical legal research method. Based on the results of the study, the return of criminal assets at the Gianyar District Prosecutor’s Office is carried out in two ways, namely being taken by the owner of the goods by showing proof of ownership of the goods or a power of attorney (if the person taking it is not the original owner), or being delivered directly by the Gianyar District Prosecutor’s Office to the owner of the goods. In addition, the activities of returning criminal assets carried out at the Gianyar District Attorney’s Office have been in accordance with the principle of transparency, as indicated by the openness of information on evidence provided by the Gianyar District Attorney’s Office through the official website of the Gianyar District Attorney’s Office and the official social media of the Gianyar District Attorney’s Office.